Improving Students' Understanding and Learning Outcomes in Algorithms through Scratch-Based Interactive Learning Media - Mahdiyah Mahdiyah; Priyanto Priyanto; Ibnu Hartopo (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2025)
This research aims to develop and evaluate the effectiveness of a learning medium based on the visual programming language Scratch in enhancing tenth-grade students' understanding and learning outcomes of algorithmic concepts at SMAN 32 Jakarta. The study is motivated by the low level of student engagement during the learning process, primarily attributed to monotonous conventional teaching methods, limited student autonomy in learning, and the lack of interactive and engaging instructional media. Notably, supporting infrastructure, such as laboratories and technological devices, is already in place. The study employed a Research and Development (R&D) approach using the ADDIE model, with experimental testing through a Pre-test Post-test, Control Group design. Research instruments included questionnaires and learning outcome tests, with data analyzed using mean difference tests. Based on validation from experts and student feedback, the Scratch-based media was deemed highly feasible. Experimental results revealed a significant improvement in the learning outcomes of the experimental group compared to the control group, with a gain score reaching 72.4% by the second session. These findings indicate that Scratch-based instructional media is both feasible and effective in improving students' comprehension and achievement in algorithmic material. Therefore, it is recommended as a strategic alternative for teaching informatics.